Heat map showing the coefficient of variation for multivariable analysis according to median CRP result, sex, age, ethnicity, deprivation and BMI. - Alex Gough (16734033) (2025)
Blue colours represent lower values of CV and red colours represent higher values of CV. Age is in years; CRP is in mg/L, deprivation score is Townsend deprivation score. Age < 20 excluded.Total N aged 20-60 = 142,970; Total N aged >60 = 261,566.